Identification of microplastics by FTIR and Raman microscopy: a novel silicon filter substrate opens the important spectral range below 1300 cm−1 for FTIR transmission measurements - Kaeppler, Andrea; Windrich, Frank; Loeder, Martin G. J.; Malanin, Mikhail; Fischer, Dieter; Labrenz, Matthias; Eichhorn, Klaus-Jochen; Voit, Brigitte (Analytical and Bioanalytical Chemistry, 2015)
The presence of microplastics in aquatic ecosystems is a topical problem and leads to the need of appropriate and reliable analytical methods to distinctly identify and to quantify these particles in environmental samples. As an example transmission, Fourier transform infrared (FTIR) imaging can be used to analyze samples directly on filters without any visual presorting, when the environmental sample was afore extracted, purified, and filtered. However, this analytical approach is strongly restricted by the limited IR transparency of conventional filter materials. Within this study, we describe a novel silicon (Si) filter substrate produced by photolithographic microstructuring, which guarantees sufficient transparency for the broad mid-infrared region of 4000–600 cm-1. This filter type features holes with a diameter of 10 μm and exhibits adequate mechanical stability. Furthermore, it will be shown that our Si filter substrate allows a distinct identification of the most common microplastics, polyethylene (PE), and polypropylene (PP), in the characteristic fingerprint region (1400–600 cm-1). Moreover, using the Si filter substrate, a differentiation of microparticles of polyesters having quite similar chemical structure, like polyethylene terephthalate (PET) and polybutylene terephthalate (PBT), is now possible, which facilitates a visualization of their distribution within a microplastic sample by FTIR imaging. Finally, this Si filter can also be used as substrate for Raman microscopy—a second complementary spectroscopic technique—to identify microplastic samples. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2022-04-14
Keywords: Filter substrate; FTIR imaging; Microplastic identification; Raman; Silicon filter